The ark and beyond : the evolution of zoo and aquarium conservation - Rabb, George B. (George Bernard), 1930-2017; Minteer, Ben A., 1969-; Maienschein, Jane; Collins, James P. (Convening science., 2018)
Scores of wild species and ecosystems around the world face a variety of human-caused threats, from habitat destruction and fragmentation to rapid climate change. But there is hope, and it, too, comes in a most human form: zoos and aquariums. Gathering a diverse, multi-institutional collection of leading zoo and aquarium scientists as well as historians, philosophers, biologists, and social scientists, 'The Ark and Beyond' traces the history and underscores the present role of these organizations as essential conservation actors.